2009
DOI: 10.1007/s00442-009-1372-3
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous Kentucky coffeetree: megafaunal fruit sinking to extinction?

Abstract: The Kentucky coffeetree (Gymnocladus dioicus, Fabaceae) is an ecological paradox. A rare tree in nature in eastern and central North America, G. dioicus produces legumes that are only known to be dispersed by water, but appear similar to fruits consumed and dispersed by elephants and rhinoceros. One would expect the pods to be consumed by livestock, but the pulp and seeds are toxic to cattle and sheep. We examine the puzzle of G. dioicus dispersal in light of its other reproductive and life history characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…For example, woody species that are adapted to megafauna dispersal (67) may still be experiencing slow declines (90), depending on whether megafauna have been substituted by smaller wild animals, domestic livestock, or humans. Similarly, coevolution with the recently exterminated moa and elephant birds, flightless ratite birds 20-500 kg (91), can explain some remarkable idiosyncrasies of New Zealand and Madagascar vegetation, especially the high representation of "wire plants," a growth form likely to have reduced the foraging efficiency of moa, thus providing protection from browsing (92)(93)(94).…”
Section: Evidence Of Large-herbivore Impact From the Paleoecological mentioning
confidence: 99%
“…For example, woody species that are adapted to megafauna dispersal (67) may still be experiencing slow declines (90), depending on whether megafauna have been substituted by smaller wild animals, domestic livestock, or humans. Similarly, coevolution with the recently exterminated moa and elephant birds, flightless ratite birds 20-500 kg (91), can explain some remarkable idiosyncrasies of New Zealand and Madagascar vegetation, especially the high representation of "wire plants," a growth form likely to have reduced the foraging efficiency of moa, thus providing protection from browsing (92)(93)(94).…”
Section: Evidence Of Large-herbivore Impact From the Paleoecological mentioning
confidence: 99%
“…comm., 2008), making it a pest that is removed from pastures. It is tempting to speculate that this species, similar to a North American legume (Gymnocladus dioicus (L) K. Koch, Fabaceae), was originally adapted to megafaunal disclimaxes 1-30 million years ago when the hemisphere hosted a large fauna of large herbivorous mammals (Zaya & Howe 2009). Unpalatability to ungulates and the plasticity of S. donnell-smithii reproduction, including greatly increased fecundity and aril quality in open habitats (McDiarmid et al 1977), suggest that the ecology of this tree reflects a much longer history in highly disturbed habitats than the short history of human disturbances would allow.…”
Section: Discussionmentioning
confidence: 99%
“…The most pressing question, then, is how similar seed dispersal by bovids and elephants must be in order for bovids to help maintain viable populations of elephant-dispersed species if the elephants are functionally extinct. On the one hand, researchers in the Americas have suggested that comparatively limited dispersal by water (GuimarĂŁes et al 2008, Zaya andHowe 2009) or scatter-hoarding seed predators ) may have rescued American megaherbivore-dispersed trees from extinction. Particularly if landscape-level negative density-dependent forces are at play (e.g., Hirsch et al 2012), low levels of dispersal by bovids and other frugivores may be able to maintain tree populations.…”
Section: August 2015mentioning
confidence: 99%